Positive Influence of 177Lu PSMA-617 Therapy on Bone Marrow Depression Caused by Metastatic Prostate Cancer. (June 2016) - Schlenkhoff, Carl Diedrich; Gaertner, Florian; Essler, Markus; Schmidt, Matthias; Ahmadzadehfar, Hojjat
Abstract : Abstract: A 75-year-old man with castrate-resistant prostate cancer and increasing prostate-specific antigen (PSA) level developed severe bone marrow depression during 223 Ra radionuclide therapy. Because of this, he was treated with Lu-PSMA in compassionate use for this not-yet-approved therapy. At the beginning of Lu-PSMA therapy, repeated blood transfusions (BT) were necessary. Six months after the last BT, after 3 cycles of Lu-PSMA, his blood count stabilized. He required no further BTs and his PSA level remained lowered.